Problema Pendidikan dan Dosen Penggerak - Anwar, Hairil; Fattah, Abdul; Mustain, Mustain (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
Education is a moral action that aims to increase individual potential and the progress of society. Education has always been an issue that involves all parties, and Indonesia prioritizes its implementation. However, the quality of education in Indonesia is worrying, with various complex problems, including curriculum problems, educational inequality, teacher placement, and low teacher quality. Apart from that, there are challenges in learning methods, inadequate facilities and infrastructure, and high education costs. In this context, the role of lecturers as drivers of education is key in improving the quality of education. Lecturers have a role in motivating students, providing guidance, and directing learning, especially in the Independent Campus era which frees students to study outside the classroom. Lecturers also play a role in generating student motivation, which is an important factor in learning achievement.